Analysis of Determinants of Increasing Urbanization in Asean Developing Countries in the Perspective of Islamic Economics (Panel Data Analysis 2018-2023) - Pitaloka, Winda; Anggraeni, Erike; Bahtiar, Muhammad Yusuf (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2025)
The Impact of Urbanization on Major Cities in Developing ASEAN CountriesThe influx of urbanization in developing ASEAN nations has significantly transformed major cities into hubs for commerce, technology, and education, consequently fostering national economic growth. However, unchecked rates of urbanization also present substantial challenges for urban populations. These include densely populated settlements, environmental degradation, and the diminishing availability of public services and infrastructure. This research aims to analyze the determinants contributing to the increasing rate of urbanization in several developing ASEAN countries. Specifically, it investigates the influence of economic growth and minimum wage levels on the escalating number of individuals migrating to urban areas within the ASEAN region, examined through the lens of Islamic economics. The study seeks to provide insights into the key economic factors driving urbanization in this context, while also considering principles and perspectives from Islamic economic thought. This research employs a quantitative method utilizing secondary data, which will be processed using the EViews software. Panel data regression analysis will be conducted to examine the relationships between the variables under investigation. The panel data regression analysis revealed that economic growth did not have a statistically significant impact on the increase in urbanization levels across the ASEAN countries examined. In contrast, the minimum wage demonstrated a statistically significant positive influence on the rise of urbanization within the region. Furthermore, the findings indicated that economic growth and minimum wage, when considered together, The rapid increase in urbanization in the ASEAN countries studied is strongly influenced by significant interactions between these factors.